Insertar en el código orgánico integral penal la normativa que sancione a los progenitores o ascendientes de un menor de edad por su utilización como instrumento para el comercio, tenencia y transporte de sustancias estupefacientes y psicotrópicas - Aguilar Granda, Stalin Oswaldo (2016)
Today we can reveal as the traffic and consumption of drugs constitute a threat to the progress of our society, since drugs engender violence, crime, exploitation, where are involved, children, and adolescents as a means of obtaining easy by distributing money, marketing of illegal drugs, and must carry out an investigation of socio-legal problem, in order to find urgent solutions that apply to the prevention and criminalization of such acts. The current situation faced by minors to be exploited for the sale of narcotic and psychotropic substances, violates their rights established in the Constitution of Ecuador and the code on children and adolescents, to involve them to commit unlawful acts, their well-being, their social, family environment, is affected, since to perform those acts, minor will immerse in the world of the drug which it will be difficult to leave probably in the future it will repeat it becoming a vicious circle, and like its parent will find an easy way to get money through distribution, marketing of drugs There is a legal vacuum in criminal law regarding sanctions that should be imposed a penalty to parents or ancestors of a minor by its use for trade, possession and transportation of narcotic and psychotropic substances. So many children have become an easy way for trade, possession and transportation of narcotic and psychotropic substances, and which are used by their own parents by means of threats, with the purpose of evading justice because there is no sanction rules, hiding behind through the minors to commit unlawful acts. There is a need for comprehensive Penal organic code, insert the regulations that punish parents or ancestors of a minor by use for trade, possession and transportation of narcotic and psychotropic substances.